Impact of POU3F4 mutation on cochlear development and auditory function - Jiong Dang; Panpan Bian; Chao Chen; Chi Chen; Wenqi Shan; Luhang Cai; Yong Li; Huan Tan; Baicheng Xu; Minxin Guan; Yufen Guo (Cell Communication and Signaling, 2025)
Abstract Background Hearing loss, a major public health issue, affects 1.33 per 1,000 live births worldwide. Genetic factors contribute to over half of congenital cases, with X-linked inheritance accounting for 1–5%. POU3F4 mutations are associated with approximately 50% of X-linked non-syndrome hearing loss cases. POU3F4 plays a critical role in cochlear development by regulating otic mesenchyme cell differentiation. The study investigates the impact of a novel POU3F4 p.E294G mutation on cochlear structure and function using cellular and animal model. Methods The study utilized immortalized lymphoblastoid cell lines, POU3F4 overexpressed HEK293 cells and generated Pou3f4 knock-in (Pou3f4KI) mice via CRISPR/Cas9 to introduce the p.E294G mutation. Alterations in expression and subcellular localization of POU3F4 were detected at the cellular level. Auditory function was assessed using auditory brainstem response testing. Cochlear structure was analyzed through histology, immunohistochemistry, scanning electron microscopy, and transmission electron microscopy. RNA sequencing, qPCR and Western blot were conducted to evaluate gene expression and mitochondrial function. Results The transcription of POU3F4 was abnormal and the expression was normal in lymphoblastoid cell lines. Abnormal nuclear localization of POU3F4 p.E294G was found in overexpressed HEK293 cells. Pou3f4KI mice exhibited cochlear malformations, including modiolus hypoplasia and reduced stria vascularis cell populations. Auditory testing revealed progressive hearing loss. Pou3f4 affect mitochondrial protein expression by affecting the expression of TFAM. Mitochondrial dysfunction was evident, with reduced oxidative phosphorylation (OXPHOS) complex assembly and activity, decreased ATP levels. The level of reactive oxygen species, mitochondrial fission and apoptosis in cochlea were elevated. Conclusions The POU3F4 p.E294G resulted in abnormal nuclear localization. Pou3f4 mutant disrupts cochlear development and function, impairs mitochondrial integrity, induces oxidative stress, and promotes apoptosis, leading to progressive hearing loss. The findings enhance the understanding of POU3F4-related hearing loss mechanisms and highlight the importance of early genetic screening and audiological monitoring.